The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1111/j.1360-0443.1975.tb00030.x
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Assessment of the T.V. Film “The Drug Takers”

Abstract: Tlie Granada T.V. filtn "The Drug Takers" was made to present fads about drug abuse in an unsemational, rational way. The effects of the film on a sample of school children was assessed using a questionnaire and the main finding was that the fitm had no significant effect on any of the attitudes assessed. Possible reasons for this are examined, which imply a different approach to future educational projects in this field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Most studies included in the review were conducted in the United States. Countries other than the United States were Canada [206-208], Australia [207-212], Brazil [213], the Netherlands [214], New Zealand [29], Norway [209,215,216], the United Kingdom [28,209,217], Germany [207], and Switzerland [218]. Moreover, 1 systematic review included 7 studies from the United States, and 1 from Norway [216].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies included in the review were conducted in the United States. Countries other than the United States were Canada [206-208], Australia [207-212], Brazil [213], the Netherlands [214], New Zealand [29], Norway [209,215,216], the United Kingdom [28,209,217], Germany [207], and Switzerland [218]. Moreover, 1 systematic review included 7 studies from the United States, and 1 from Norway [216].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, 1 study in the United Kingdom having subjects from 7 schools included 1 school with predominantly black students and the rest with mostly white students [217]. Another UK school-based study reported their participants were chosen to have a balance between both sexes, residence in rural and urban areas, and varying intellectual abilities [28]. A total of 4 studies specifically evaluated interventions on adolescent girls [220,223,234,235].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations